A Finite Element Analysis of Bottom Structure of LCT Converted from SPOB - Pawara, Muhammad Uswah; Alamsyah, Alamsyah; Kusuma, I Putu Arya; Wulandari, Amalia Ika; Ikhwani, Rodlian Jamal; Arifuddin, Mursid Nugraha (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2023)
SPOB (Self-Propelled Oil Barge) ship is useful for transporting oil. Due to certain requests, the owner and operator have converted SPOB into LCT. If before the conversion the ship transported oil, now the ship is transporting vehicles or heavy equipment on the deck. after the transfer of function from a SPOB ship to an LCT (Landing Craft Tank) ship, the cargo transported is different, the bottom is the part that is submerged in the water, so this part is vulnerable. Therefore, it is necessary to systematically predict the weight of the load that can be held by the ship at the bottom, this is so that there is no damage to the structure at the bottom of the ship which can harm the company from the ship owner. The purpose of this study is to find the maximum stress and strain that can be accepted by the ship and the value of the stress ratio (safety factor) in the bottom construction using the finite element method. The results obtained from the maximum stress and strain of the ship after and before conversion of 96.349Mpa, 272.56 Mpa, and 0.0013628 mm, 5.042 x 10-4 mm, safety factor according to BKI after and before conversion obtained 3.624 and 1.057, the safety factor according to the material criteria is 3.685 and 1.172, respectively, for the maximum deformation of the ship, the safety factor is 6.328 and 3.287 respectively